Minimizing the duration of laser Doppler flowmetry recordings while maintaining wavelet analysis quality: A methodological study - Reynès, C.; Vinet, A.; Maltinti, O.; Knapp, Y. (Microvascular research, 2020)
Recording oscillations in cutaneous blood perfusion using laser Doppler flowmetry (LDF) is of common use in clinical research, due, mainly, to its non-invasive nature. Detailed information about the vascular tone in different frequency bands and the related physiologic compartment can be inferred from wavelet analysis (WA) of an LDF signal. However, little is known about the minimal recording duration required to generate a proper representation of the frequency content of such signals. To address this question, the three lowest frequency bands (i.e. myogenic, neurogenic and endothelial) of the LDF wavelet power spectrum were studied to define the shortest recording duration needed to perform a quality WA. Sixty-five healthy participants were included for 20 min of basal LDF recording on forearm and dorsum of the foot. Recordings were short cut every minute and compared to the 20-min reference recording that is generally used in the literature. Our results indicate that minimum 10 min recordings are required for analysis of myogenic events, whatever the anatomical site. On the forearm, LDF recordings lengths should be at least 15 min and 10 min for the neurogenic and endothelial bands, respectively. On the foot, 13 min of LDF recording is required to assess neurogenic and endothelial bands. Depending on the aim of any given study involving healthy subjects, LDF recordings need to last at least 15 min on forearm and 13 min on the foot to maintain a quality WA on low-frequency bands. •LDF should be performed for at least 15 min f006Fr a high quality Wavelet Analysis.•The neurogenic spectral band takes the longest amount of time to capture.•Recording duration is dependent on the anatomical site.•Only ten minutes recordings are necessary in men regardless the anatomical site.